Photoinduced Borylation Reactions: An Overview. Issue 1 (8th December 2020) - Yadagiri, B.; Daipule, Komal; Singh, Surya Prakash
Abstract: The photochemical reactions perform a progressively important role in the field of green chemistry and organic synthesis from the last decades. It has always been considered as eco‐friendly, inexpensive, most abundant and endlessly renewable energy source. The organoboronic acids and esters occupy a central position in the field of chemistry so the development of novel methodology for the preparation of organoboron compounds is essential. In recent years, visible light‐induced photoredox catalysis has created a more influence on the preparation of different organoboron compounds using novel synthetic methodologies with very mild and eco‐friendly conditions. In this review, we have provided a brief overview of preparation of organoboronic acids or esters from aliphatic, aromatic C−H/C−X and other functional groups by photoredox methodology. Abstract : Preparations of organoboronic acids or esters from aliphatic and aromatic group are regarded as building blocks for organic molecule synthesis. Conventional method involves many disadvantages such as less scope and functional group tolerance. Due to a number of advantages posed by photoredox catalysis, it plays an important role in synthetic chemistry.